Serum lipid profile in patients with primary fibromyalgia - Kaoud, Enas J.; Daoud, Munaf S.; Alosami, Mohammed H. (Journal of the Faculty of Medicine Baghdad, 2011)
Background: Fibromyalgia syndrome (FMS) is a chronic musculoskeletal disorder characterized by wide spread body pain, chronic fatigue,